Challenging the Spatial and Temporal Constraints of the Body: The Online/Offline Presence of Bodybuilders in India. Issue 4 (1st December 2018) - Baas, Michiel
Abstract: This article focuses on the way Indian bodybuilders negotiate spatial and temporal constraints offline (in "real" life) as well as online. These bodybuilders, who often make a living as personal trainers, display and advertise their bodies online in various stages of being and becoming, ranging from off-season/bulking stage to on-season/cutting stage when they start making the body ready for competition. This article discusses what it means to have an offline body that represents one temporal stage while at the same time maintaining a plethora of such (previous) stages online, to be consulted by others (e.g., aspiring bodybuilders, clients, and admirers). This article shows how these bodily representations and realities interact with various expectations and idealizations of the male body. The article proposes to think through the (re)presentation of these bodies via the dyad of im/mortality. The immortal body here is one that is multiple and can be accessed/consulted online by others at all times. The mortal body, in contrast, exists in or represents reality offline, referencing a state of becoming and eventual unbecoming. This article explores the tension produced through this opposition between questions of mortality offline and the quest for immortality online. While this article takes this oppositional structure as its point of departure, its ultimate aim is to upset the various dyads it builds on to show that the (bodybuilder's) body always occupies multiple spheres across time and space, ultimately producing a hybridization of the real.